Effect on TEG performance for waste heat recovery of automobiles using MgO and ZnO nanofluid coolants - Karana, Dhruv Raj; Sahoo, Rashmi Rekha (Elsevier Ltd, 2018)
Present study deals with the theoretical analysis for the performance comparison of automotive waste heat recovery system with EG-W, ZnO and MgO nanofluidas coolants for TEG system. Effects on performance parameters i.e power output, conversion efficiency and circuit voltage of TEG system with exhaust inlet temperature, total area of TEG, Reynolds number and particle concentration of nanofluids for TEG system have been investigated. Theoretical performance analysis revealed enhancement in output power, conversion efficiency and voltage of the TEG system for MgO nanofluid, followed by ZnO and EG-W coolants. The power output and the conversion efficiency using 1% vol. fraction MgO nanofluid at an inlet exhaust temperature of 500K, were enhanced by 11.38% and 10.95% respectively, as compared to EG-W coolants. The further increase in nanofluid concentration exhibited a progressive effect on output performance of the TEG system. Further analysis shows that there exists an optimal total area of TEGs for maximum output performance of the system. With MgO nanofluid as a coolant, total area of TEGs can be reduced by up to 33% as compared to EG-W, which would bring significant convenience for the arrangement of TEGs and reduce the cost of TEG system.
Keywords: Circuit voltage; Conversion efficiency; Nanofluid; Reynolds number; Thermoelectric generator; Waste heat recovery